A new perspective on the internalization process of organizational culture: Self-directed identity work - 정식; Chung, 구혁 (Korean Journal of Industrial and Organizational Psychology, 2022)
The existing studies on organizational culture, drawn on the social learning theory, have the somewhat passive and reactive perspective on new-comers’ socialization process; that is, they have considered that new-comers often learn organizational culture in the provision of compensation or reinforcement. According to Social Psychology literature, however, human beings are usually viewed as those who will develop perception of themselves (i.e., ‘self’), who can evaluate the level of fit or congruence between their own ‘self’ (or value) and social requirements, and who may actively determine the degree to which they conduct behaviors corresponding to something socially-demanded. In the present research, we rely on the concept of ‘self’, introduce the concepts of ‘self and organizational identity’ to the literature of organizational culture, and adapt the concept of ‘identity work’ - which refers to employees’ proactive endeavor to reconcile their ‘self’ with organizational culture in the case of cultural conflict between the two - to attempt to further understand the internalization process of organizational culture. Beyond the bifurcated existing theoretical framework of employees’ behaviors toward organizational culture (i.e., either acceptance or exit; c.f., attraction-selection-attrition theory), our discussion presents a more balanced view on the interactive internalization process of organizational culture.